The Impact of The Auditory, Intellectually, Repetition (Air) Model on Social Studies Learning Outcomes - Harry Indah Kartika; Hermansyah H; Susanti Faipri Selegi (Universitas Pendidikan Indonesia (UPI), 2023)
The objective of this study was to ascertain and describe the learning outcomes in the subject of Social Studies (IPS) after the implementation of the Auditory, Intellectually, Repetition (AIR) model in Grade IV at SDN 76 Palembang. The research methodology employed was experimental, utilizing a true experimental design with a pretest-posttest control group design. The research analysis revealed that the average pre-learning outcomes for students in the experimental group were 66.16, which improved significantly to 87.3 after the implementation of the Auditory, Intellectually, Repetition (AIR) model. In contrast, the average pre-learning outcomes for students in the control group were 65.34, with a modest increase to 69.22 after traditional teaching methods without the use of the AIR model. Statistical calculations yielded a calculated t-value (t-test) of 1.79, surpassing the critical t-value (t-table) of 1.67. Consequently, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. This signifies that the implementation of the Auditory, Intellectually, Repetition (AIR) model led to improved student learning outcomes in the subject of IPS at SDN 76 Palembang.